Analysis of porous materials for transpiration cooled heat flux sensor development - Hufgard, F; Löhle, S; Hermann, T; Schweikert, S; McGilvray, M; Von Wolfersdorf, J; Steelant, J; Fasoulas, S (2018)
The Non-Integer System Identification (NISI) method is an useful tool for the determination of surface heat flux from in-depth temperature data even in transpiration cooled environments. Recently it was demonstrated that in these transpiration cooled environments the surface heat flux can be determined using a measurement of the plenum pressure changes in the gas reservoir at the rear side of the porous structure for the Non-Integer System Identification (NISIp). This paper presents fundamental experiments required for the identification of susceptibilities with respect to the thermophysical and fluid properties. Test results with two different porous materials are compared: zirconium diboride and carbon/carbon. The experimental setup for both systems and the respective resulting impulse responses over varying coolant mass flows are presented and discussed in this paper. It was found that the pressure impulse responses of the ZrB2 system is more sensitive to coolant mass flow rate changes than the C/C system with respect to both response time and amplitude pressure. However, the absolute response time of the C/C system was significantly shorter for all tested flow rates.